Two pediatric patients with hemiplegic migraine presenting as acute encephalopathy: case reports and a literature review - Xiang, Yu; Li, Fei; Song, Zhenfeng; Yi, Zhi; Yang, Chengqing; Xue, Jiao; Zhang, Ying (Frontiers in Pediatrics, 2023)
Introduction Hemiplegic migraine (HM) is a rare subtype of migraine. HM in children may be atypical in the initial stage of the disease, which could easily lead to misdiagnosis. Methods We report two cases of atypical hemiplegic migraine that onset as an acute encephalopathy. And a comprehensive search was performed using PubMed, Web of Science, and Scopus. We selected only papers that reported complete clinical information about the patients with CACNA1A or ATP1A2 gene mutation. Results Patient #1 showed a de novo mutation, c.674C>A (p. Pro225His), in exon 5 of the CACNA1A gene. And patient #2 showed a missense mutation (c.2143G>A, p. Gly715Arg) in exon 16 of the ATP1A2. Together with our two cases, a total of 160 patients (73 CACNA1A and 87 ATP1A2) were collected and summarized finally. Discussion Acute encephalopathy is the main manifestation of severe attacks of HM in children, which adds to the difficulty of diagnosis. Physicians should consider HM in the differential diagnosis of patients presenting with somnolence, coma, or convulsion without structural, epileptic, infectious, or inflammatory explanation. When similar clinical cases appear, gene detection is particularly important, which is conducive to early diagnosis and treatment. Early recognition and treatment of the disease can help improve the prognosis.